A major plant practice at Magna Prime Packaging Corporation Bldg. 10A CTIP Compound Ortigas Ave. Extension, Km 19 Rosario, Pasig City - Micabalo, Chirlen Saballa (2008)
The trainee spent her 288-hour practicum at the Magna Prime Packaging Corporation (MPPC) at Ortigas Avenue extension, Pasig City last April-March 2006. The trainee was allowed to participate in the plant?s operations performing the job of a quality control officer. Few of her activities were sampling and inspecting of the raw materials and packaging materials, production/line monitoring, and quality control analysis. Each of these activities was given a couple of days for the intern to learn the principles and processes of different tests and sampling methods in the plant. The remaining days were then spent going through the routines where the author took part in the activities herself. The plant practice has provided the intern an avenue for applying the principles she has learned in the university and applies these theories as she goes through the technical processes. It also enabled her to establish good working relationships with employers and personnel who contributed to her experience. This manuscript shall provide a written output combining the methodical tests and theories she has learned in the plant and the principles involved. This manuscript shall be a reliable source for any one who wishes to know how it is working in a plant packaging powdered milk products
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2008
Keywords: Physicochemical